2022
DOI: 10.1007/s10549-022-06623-2
|View full text |Cite
|
Sign up to set email alerts
|

Association of markers of tumor aggressivity and cognition in women with breast cancer before adjuvant treatment: The Thinking and Living with Cancer Study

Abstract: Purpose: Tumor features associated with aggressive cancers may affect cognition prior to systemic therapy. We evaluated associations of pre-treatment cognition and tumor aggressivity in older breast cancer patients.Methods: Women diagnosed with non-metastatic breast cancer (n=705) ages 60-98 were enrolled from August 2010-March 2020. Cognition was measured post-surgery, pre-systemic therapy using self-reported (FACT-Cog Perceived Cognitive Impairment [PCI]) and objective tests of attention, processing speed, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 44 publications
(32 reference statements)
0
5
0
Order By: Relevance
“…A score less than 54 is indicative of cognitive impairment and can well distinguish between CRCI and non-CRCI. 24 , 25 The Cronbach's α coefficient of the CogPCI in this study was 0.947.…”
Section: Methodsmentioning
confidence: 48%
“…A score less than 54 is indicative of cognitive impairment and can well distinguish between CRCI and non-CRCI. 24 , 25 The Cronbach's α coefficient of the CogPCI in this study was 0.947.…”
Section: Methodsmentioning
confidence: 48%
“…35 The presystemic therapy differences in IL-6 levels between survivors and controls also add to the body of evidence that cancer may have important effects on inflammation and cognition even before systemic therapy begins. 21,22,37,38 The finding that survivor-control differences in factors including comorbidity and obesity slightly attenuated IL-6 mediation effects on cognition suggests that a preexisting proinflammatory state may contribute to the risk of developing breast cancer and/or cognitive decline. 21 Prospective studies with assessments before and after cancer would be necessary to fully explore this possibility.…”
Section: Discussionmentioning
confidence: 99%
“…This will be important to examine further, because others have found that radiotherapy and/or chemotherapy induce cellular damage that increases peripheral inflammation and cognitive problems and that HER2-positive cancers are associated with cognitive problems even before treatment. 19,24,38 Fifth, because we added blood collection to an already established cohort, not all survivors had plasma data before systemic therapy.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations